ANALISIS KECEPATAN ALIRAN UDARA PADA GEDUNG BERTINGKAT KARENA PENGARUH PENGHALANG DI DEPANNYA - Susanto, Joni; Dafik, D; Fatahillah, Arif (KadikmA, 2015)
Abstract. The air flow velocity is one of many factor which should be considered in building a skyscraper. This is because the air flow velocity can affect the comfort of house room. The method which is used to solve the air flow analysis is a finite volume withusing Quadratic Upwind Interpolation Convective Kinematics (QUICK) discretization technique. Finite volume method is used to obtain a mathematical model of air flow velocity and QUICK is used to discretize it such that it will yield a linier equation system in a matrix of size (mn)Ã(mn). To simulate the air flow analysis is used Matlab and Fluent softwares. The result show that if the barrier is higher the air flow velocity will be decreased and if the distance of barrier is longerthe air flow velocity will be increased. It can be conclude that this analysis can be applied to have a comfort house room. Key Words : air flow velocity,mathematic model, finite volume method,QUICK